Fear of Missing Out and Digital Content Marketing as Drivers of Impulse Buying in Social Commerce Platforms - Nadia Gita Aresti; Amelia Kristofani; Dewi Alesha Miller (Ilomata International Journal of Social Science, 2026)
This study investigates how fear of missing out (FoMO) and content marketing drive impulse buying among Generation Z skincare consumers on TikTok Shop in Jakarta, addressing the need for clearer insight into psychological and marketing mechanisms within Indonesia’s rapidly evolving social commerce landscape. The research directly compares the relative impact of internal (FoMO) and external (content marketing) drivers within a single empirical model—an area previously underexplored in the context of Indonesia’s rapidly expanding social commerce. Using a quantitative, cross-sectional online survey, data were collected from 405 TikTok Shop skincare buyers aged 18–28 in Jakarta and analysed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that both FoMO and content marketing significantly increase impulse buying, with content marketing demonstrating the stronger effect. These findings demonstrate that both engaging content and FoMO-based strategies can increase impulse buying among Generation Z skincare consumers. The study contributes theoretically by providing empirical evidence that both psychological (FoMO) and marketing (content) drivers jointly influence impulse buying in social commerce platforms, highlighting the importance of integrating internal and external factors within explanatory models of consumer behaviour. Despite its insights, limitations include self-reported data and focus on one city; future research should use behavioural data and expand to other regions and demographics.